Rap1p requires Gcr1p and Gcr2p homodimers to activate ribosomal protein and glycolytic genes, respectively. - Deminoff, S J (2001)
Efficient transcription of ribosomal protein (RP) and glycolytic genes requires the Rap1p/Gcr1p regulatory complex. A third factor, Gcr2p, is required for only the glycolytic (specialized) mode of transcriptional activation. It is recruited to the complex by Gcr1p and likely mediates a change in the phosphorylation state and/or conformation of the latter. We show here that leucine zipper motifs in Gcr1p and Gcr2p (1LZ and 2LZ) are each specific to one of the two activation mechanisms-mutations in 1LZ and 2LZ impair transcription of RP and glycolytic genes, respectively. Although neither class of mutations causes more than a mild growth defect, simultaneous impairment of 1LZ and 2LZ results in a severe synthetic defect and a reduction in the expression of both sets of genes. Intracistronic complementation by point mutations in the charged e and g positions confirmed that Gcr1p/Gcr1p and Gcr2p/Gcr2p homodimers are the forms required for the different roles of the activator complex. Direct heterodimerization between 1LZ and 2LZ apparently does not occur. Dichotomous Rap1p activation and its striking requirement for distinct homodimeric subunits give cells the capacity to switch between coordinated and uncoupled RP and glycolytic gene regulation.